2015
DOI: 10.15832/ankutbd.25211
|View full text |Cite
|
Sign up to set email alerts
|

A Heterosis Study for Some Agronomic Traits in Oat

Abstract: The benefits of increased hybrid vigor, which often occur crossing unrelated plants or animals, have been recognized for centuries. In this study, hexaploid oat genotypes E44, K1, and A52 belong to A. sativa and A45 belonging to A. byzantina species were crossed. Heterosis, heterobeltiosis and standard heterosis values were calculated for 11 traits on 12 hybrids belong to K1 x E44 cross (ten hybrids), K1 x A45 cross (one hybrid) and K1 x A52 cross (one hybrid) with the parents. According to the results, parent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
2
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
(5 reference statements)
6
2
0
1
Order By: Relevance
“…Genzania had the highest average, reached 69.6 and 76.0 grains head -1 , significantly higher than all other cultivars in the first season, and higher than Shafa and Carrolup in the second season, while Carrolup had the lowest average, reached 39.0 and 43.4 grains head -1 for the two seasons respectively. This finding agree with the results found by Siloriya et al, (22), and Dumlupinar et al, (14) about the different of grains head -1 in oat genotypes. Foliar application of boron in the first season with concentrations of 50 and 100 ppm resulted in significant increases number of grains head -1 than in control with 15.08% and 16.52% respectively, but the concentrations 50 and 100 ppm did not differed significantly ( Table 6).…”
Section: Number Of Grains Head -1supporting
confidence: 94%
See 1 more Smart Citation
“…Genzania had the highest average, reached 69.6 and 76.0 grains head -1 , significantly higher than all other cultivars in the first season, and higher than Shafa and Carrolup in the second season, while Carrolup had the lowest average, reached 39.0 and 43.4 grains head -1 for the two seasons respectively. This finding agree with the results found by Siloriya et al, (22), and Dumlupinar et al, (14) about the different of grains head -1 in oat genotypes. Foliar application of boron in the first season with concentrations of 50 and 100 ppm resulted in significant increases number of grains head -1 than in control with 15.08% and 16.52% respectively, but the concentrations 50 and 100 ppm did not differed significantly ( Table 6).…”
Section: Number Of Grains Head -1supporting
confidence: 94%
“…These differences could be due to the differences genotype of cultivars that led to the different efficiency of metabolism and transport of storage materials during the grain filling period. Dumlupinar et al, (14) and Chappell et al, (11) found that oat genotypes differed in grain weight. The data shows that there were negative effects of ethephon on the Single grain weight ( Table 7).…”
Section: Single Grain Weight (Mg)mentioning
confidence: 98%
“…Heterobeltiosis for leaf area was found in the ranged -17.48 (JHO851 x OS403) to 24.04 (JHO-99-2 x OL125) of heterobeltiosis was recorded among all the F 1 's for stem girth. The expression of heterosis of similar magnitude for this attribute has also been reported by Kapoor and Bajaj (2013), Mishra et al, (2014) and Dumlupinar et al, (2015).…”
Section: Resultssupporting
confidence: 86%
“…Kent x JHO-99-2, Kent x JHO851, Kent x OS403, Kent x UPO212, OS6 x JHO-99-2, JHO-99-2 x JHO851, JHO851 x OL125, JHO851 x UPO212, OS403 x OL125, OL125 x NDO612 and UPO212 x NDO612 noted positive and significant heterosis over better parent for more number of leaves per plant and hybrid JHO-99-2 x OL125 recorded negative significant heterosis over better parent for this character. Estimates of positive heterosis for this character were earlier reported by Dumlupinar et al, (2015). Heterobeltiosis for leaf area was found in the ranged -17.48 (JHO851 x OS403) to 24.04 (JHO-99-2 x OL125) of heterobeltiosis was recorded among all the F 1 's for stem girth.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation